Estrategias de marketing para promocionar el turismo en el cantón Las Naves Provincia de Bolívar - Riera Castilo, Jazbeth Carolina (2021)
The tourist activity in contemporaneity where technological development is increasing on a large scale has caused significant changes both in the economy and in society; the development of new tourism products acquires a more active dynamic because it is no longer enough to just show a resource but rather to transmit an experience. That is why this research aimed to design marketing strategies to promote and improve tourism in the Las Naves canton. The surveys were applied to 60 people from the Las Naves canton, with a questionnaire of 20 closed questions that make it possible to homogenize the information and speed up the information gathering process within the time of the pandemic. The results obtained allowed to identify that in the Las Naves canton there is a high degree of knowledge of the inhabitants about the tourist attractions of the place, in such a way that 90.00% indicated that they have heard about them, so that 85% do consider to the Las Naves canton as a tourist site, the same as if they have visited at least one of the tourist places in the area. The most visited sites are El Chorrito, Piedra Grande, San Mateo waterfalls, Bellavista waterfalls, and La Canoa park, showing that 96.66% showed their willingness to visit these tourist places. The surveyed inhabitants travel preferably as a family (65.00%), learning mainly about tourist sites through social networks, so they prefer to obtain information about the attractions of the Las Naves canton through this means (58.33%).